Organisational Commitment in Educational Institutions – the Results of Empirical Research - Wziątek-Staśko, Anna; Michalik, Izabela (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To present organisational commitment as a key research category and the results of original research aimed at identifying the level of organisational commitment in educational institutions.Research Design & Methods: A literature review and empirical research conducted with the use of quantitative and qualitative methods.Findings: The empirical research showed a high level of organisational commitment among survey respondents for three components: affective, continuance and normative commitment.Implications / Recommendations: Organisational commitment enjoys growing interest in the world today. Thanks to the benefits it offers, strong organisational commitment is important for the organisations themselves and their management teams as well as science.Contribution: The level of organisational commitment was identified in three components: affective, continuance and normative commitment among employees of educational institutions.